Dental dam utilization by dentists in an intramural faculty practice - Terence A. Imbery; Caroline K. Carrico (Wiley, 2019)
Abstract Objectives From casual observation of our colleagues, only a few individuals use the dental dam for operative procedures in their faculty practice. The purpose of this study was to obtain faculty perceptions of the dental dam, quantify its utilization in their intramural faculty practice, and determine the factors that influence dental dam usage. Material and Methods A survey containing 11 questions was sent to 19 faculty members who teach full time and maintain an intramural dental practice involving operative dentistry. Thirty electronic dental health records of the 19 providers were reviewed to gather the following information from restorative procedures they completed: isolation methods, tooth location and involved surfaces, and dental restorative material. Results Overall, dental dam was utilized for 30% of all restorative procedures and was used less than 20% of the time for placement of class II and class III composite resins. Dental dam utilization rate by general dentists was 37% and 17.6% for prosthodontists. Those general dentists with prior history of military dental practice had a utilization rate of 78.6% and nonmilitary dentists only 7.6%. Eight faculty members responded to the questionnaire for a 42% return rate. Those who practiced dentistry in the military strongly agreed that the dental dam is the standard of care, improves their quality of restorative work, and should be documented in the dental record. Conclusions There were significantly different dental dam utilization rates between general dentists and prosthodontists and between dentists with prior military experience and those without.